Effect of antipyretics on polymorphonuclear leukocyte functions in children - (:unkn) unknown (My University, 2002)
The aim of this study was to investigate whether fever and antipyretic drugs had an adverse effect on human polymorphonuclear leukocyte (PMN) functions (phagocytic and intracellular killing activity). Twenty febrile children with an axillary temperature of 39-40 °C and 20 healthy children without fever were included. Polymorphonuclear leukocytes were isolated. The effects of in vitro addition of antipyretic drugs (acetaminophen, metamizole sodium, nimesulid and ibuprofen) on PMN functions were tested. Phagocytic activity was assayed by the ingestion of yeast cells by PMNs and intracellular killing activity by the ingestion of yeast cells (stained blue) killed by PMNs. PMNs derived from febrile children exhibited better phagocytic activity when ibuprofen was added. In contrast, phagocytic activity was enhanced when acetaminophen, metamizole sodium or nimesulid was added in children without fever. Intracellular killing activity was enhanced when ibuprofen or metamizole sodium was added in children without fever. We conclude the antipyretic drugs at safely achievable concentrations do not suppress PMN function in vitro. © 2002 Elsevier Science B.V. All rights reserved.
Keywords: Acetaminophen; Ibuprofen; Intracellular killing; Metamizole sodium; Nimesulid; Phagocytosis; Polymorphonuclear leukocyte